The Challenges of Green Construction in Oman - Powmya, Ayisha; Zainul Abidin, Nazirah (International Journal of Sustainable Construction Engineering and Technology, 2014)
Oman has seen rapid growth in construction industry with the blooming of many new infrastructure projects. The conventional way of approaching construction projects in the past makes introducing sustainable construction a major challenge. The country has a sound environmental law, however, the effectiveness of its implementation is unclear.Green or sustainable concept is still new to Omani people and as such many initiatives to promote the concept are necessary. In line with the green development of its neighboring countries, Oman should act fast to be at par with them. This paper explores the progress of green construction in the industryto understand how far this concept has penetrated the industry. A survey has been conducted among construction practitioners in Oman focusing on the current progress and barriers of implementation.A total of 12 barriers of implementation have been identified of which the lack of demand for green construction and lack of pressure by government are the top two.The findings suggest that many more efforts are necessary to push green construction to the forefront and the government should play a major role in this development.